Design, Simulation and Fabrication of Dual-Band Polarized Microstrip Patch Antenna - Wan Hassan, Wan Haszerila; Kasno, Mohammad ‘Afif; Rahim, Norain; Che Aziz, Siti Asma (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
A new design of a simple dual-band and dualpolarised microstrip patch antenna is presented with a single feeding. Paper present two designs to make antenna compact without much alteration results. The proposed antennas are designed, simulated and fabricated and tested to be used in dual frequency bands which are GSM900 and 1800 bands. The Design I can be operated at frequency ranges from 924MHz to 1790MHz for simulation and real measurement from 938MHz to 1837MHz. Meanwhile, the operating frequency ranges for Design II from 900MHz to 1760MHz for simulation and real measurement between 904MHz to 1775MHz. The results show the simulated and measured result are in good agreement.